2000
DOI: 10.1520/cca10470j
|View full text |Cite
|
Sign up to set email alerts
|

Specimen and Aggregate Size Effect on Concrete Compressive Strength

Abstract: Test results obtained on the effect of specimen size and aggregate size on concrete compressive strength and modulus of elasticity are presented. The concrete was prepared using 4.75, 9.5, 19.0, 37.5, and 75-mm nominal maximum size aggregate. Over 600 cylinders were cast and tested for concrete compressive strength and modulus of elasticity. Four different sizes of plastic cylinder molds were used: 150 by 300 mm, 100 by 200 mm, 75 by 150 mm, and 50 by 100 mm. The testing was carried out in accordance with ASTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Figure 3 shows the gradation curves for coarse and fine aggregates. The maximum aggregate size was 12 mm, which is acceptable for the 75 mm diameter specimens prepared for use in this study (see Issa et al 2000).…”
Section: Methodsmentioning
confidence: 97%
“…Figure 3 shows the gradation curves for coarse and fine aggregates. The maximum aggregate size was 12 mm, which is acceptable for the 75 mm diameter specimens prepared for use in this study (see Issa et al 2000).…”
Section: Methodsmentioning
confidence: 97%
“…with adequate aggregate proportioning, proper aggregate quality and proper water/cement ratio. Looking at the test results from the scientific literature [18,[35][36][37][38][39][40][41] we can see that test data show a dispersion similar to the one showed in figures 7 and 8.…”
Section: Discussionmentioning
confidence: 56%
“…By elimination, we can argue that this effect could be due to the round and smooth surface of the larger aggregates, even though more research is due on this issue. The effect of large aggregates on the behavior of concrete is not new and is still a research issue of the academic community, [40][41][42][43][44][45] among the others.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the author also pointed out that the compressive strength ratio of 150×300 mm cylinder to 100×200 mm cylinder is 0.86 [10]. Issa et al in their research conducted to evaluate the size effect of cylinders on compressive strength of concrete, used 150×300 mm, 100×200 mm, 75×150 mm, and 50×100 mm size plastic moulds to cast 600 cylinders [11]. Experimental evaluation of compressive strength and modulus of elasticity revealed that co-efficient of variation of compressive strength increased as size of cylinder decreased.…”
Section: Introductionmentioning
confidence: 99%